Feasibility Analysis of Using NIR Spectroscopy to Predict Ripeness Parameters of Red Guava Fruit (Psidium guajava L.) - Hartanto, Rezza Naftari; Pertiwi, Setyo (Jurnal Keteknikan Pertanian, 2024)
Red guava is highly preferred by Indonesians because of its delightful flavor, refreshing taste, and numerous advantages. It is a climacteric fruit, and the age at which red guava is picked affects the quality of the fruit. The estimation of the maturity parameters of red guava is physically destructive (damages the fruit). This study aimed to assess the NIR method to predict the maturity parameters of red guava fruit with wavelengths of 1000-2500 nm. Red guavas of four different picking ages were used in this study. The tested maturity parameters included firmness, moisture content, total soluble solids (TSS), acidity, and sugar-acid ratio at various harvest ages. The partial least squares (PLS) method was used for calibration and validation of NIRS data and reference data. The results of this study show that NIRS can estimate the ripeness of red guava fruit based on firmness, acidity, sugar-acid ratio, and water content. The best-estimated value for firmness parameters was obtained with pretreatment MSC factor PLS 14, resulting in r calibration of 0.94, SEP 7.20, CV 25.91%, and RPD 2.90; acidity without pretreatment factor PLS 13 obtained r calibration of 0.82, SEP 0.17, CV 24.42%, RPD 1.68; sugar acid ratio with pretreatment SNV factor PLS 10 obtained r calibration 0.75, SEP 4.03, CV 30.81%, RPD 1.51; and for moisture content using SNV pretreatment factor PLS 13, r calibration 0.88, SEP 0.95, CV 1.08%, RPD 1.95.